Crescimento de Egeria densa (Planch.) e Salvinia molesta (Mitch.) expostas a extratos aquosos de rizomas e raízes de Typha domingensis (Pers.) - Silva, Ricardo Rafael Ribeiro da (Universidade Federal de São Carlos, 2021)
Allelopathy can be used to control invasive species. The present study aimed to identify changes in the growth and development characteristics of Egeria densa (Planch.) and Salvinia molesta (Mitch.) by evaluating the basic components of the architecture (connectors and nodes) and estimating the kinetic parameters of growth (doubling time, growth coefficient and total length) from mathematical modeling. We exposed 30 macrophytes of each species for each treatment of aqueous extract (EA) of roots and rhizomes of Typha domingensis (Pers.), varying the concentration of aqueous extract by 5% (EA5), aqueous extract 10% (EA10), aqueous extract 15% (EA15) and a control group (C) at a temperature of 23 °C and 27 °C (for E. densa) and only a temperature of 23 °C for S. molesta. E. densa showed lower number of nodes at a temperature of 27 °C exposed to EA15 treatment (3.1 ± 1.3) than plants exposed to control (4.5 ± 1.3) and EA5 (5.1 ± 2.0). S. molesta had the lowest number of nodes and connectors that was identified in the treatment of EA10. The parameterization of growth for E. dense revealed that at 23 °C treatments EA5 and EA10 reduced the total length, as well, the growth coefficient (µ) for both fragments and branches. At 27 °C and treatments EA5, EA10 and EA15 there was an increase in the growth of E. densa identified by the values of total length and growth coefficient (µ). For the S. molesta macrophyte in stage one growth, growth inhibition was found, which was identified in the architecture that did not show differences between treatments and control. Furthermore, the growth parameters could not be estimated due to the non-development of the S. molesta macrophyte exposed to the treatments. In general, the growth inhibitory effect was better observed in submerged macrophytes exposed to aqueous extracts at a temperature of 23 °C than at 27 °C.
Growth of Egeria densa (Planch.) and Salvinia molesta (Mitch.) exposed to aqueous extracts of rhizome and roots of Typha domingensis (Pers.)
Keywords: Arquitetura; Efeito alelopático; Espécies invasoras; Modelagem matemática; Salvinaceae; Typhaceae; Allelopathic effect; Architecture; Invasive species; Mathematical modeling; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA DE ECOSSISTEMAS